Analytical performance and user-friendliness of five novel point-of-care D-dimer assays. (1st September 2020) - Heerink, Jorn S.; Gemen, Eugenie; Oudega, Ruud; Hopstaken, Rogier; Geersing, Geert-Jan; Kusters, Ron
Abstract: D-dimer testing combined with a clinical assessment has become a standard pathway for ruling-out venous thromboembolism (VTE). Recently, novel Point-of-Care (POC) D-dimer assays have been introduced, enabling low-volume blood sampling for rapid exclusion of VTE in a one-step procedure. We assessed the analytical validity and user-friendliness of a set of these novel POC D-dimer assays, and compared the results with a standard laboratory assay. Plasma samples were run on our reference assay (STA-Liatest D-di PLUS ® ) and five POC assays: Nano-Checker 710 ®, AFIAS-1 ® ; iChroma-II ® ; Standard F200 ® and Hipro AFS/1 ® ). After evaluating imprecision, Pearson Product-Moment correlation coefficients were calculated, Passing Bablok regression was performed and Bland-Altman plots were generated. User-friendliness was evaluated using the System Usability Scale (SUS). A set of 238 plasma samples of patients clinically suspected of VTE in general practice was available for analysis. Only one POC D-dimer assay (Nano-Checker 710) demonstrated an insufficient degree of imprecision. Pearson correlation coefficients and mean biases ranged from 0.68 to 0.93 and −165 to −53 μg/L respectively, and concordance with our reference assay varied from 71.8% to 89.5% using a 500 μg/L cut-off point. While we found considerable variation in overall user-friendliness, most devices were judged easy to use. In view of our findings regarding analytical performance and user-friendliness, we consider most of the novel POC D-dimer assays can be used in settings outside of the laboratory such as general practice, combining the possibility of multi-testing with low-volume capillary blood sampling and processing times of less than 15 min.